Geomorphological characteristics and the kinematic process of the Ganheba rock–ice avalanche in Yulong Mountain, China - Chen, Ruichen; Chen, Jian; Shi, Lulu; Cui, Zhijiu; Chen, Song (Frontiers in Earth Science, 2023)
Rock-ice avalanches have increased in recent years due to global warming. On March 12, 2004, a massive failure of rock mass (9.1×10^6 m^3) originating on the south slope of Yulong Mountain in Yunnan Province, and eventually formed the Ganheba rock-ice avalanche with the H/L ratio of 0.4. In this study, based on the remote sensing interpretation, field investigation, and 2D discrete element model, the geomorphological characteristics, sedimentary characteristics, and emplacement process of the Ganheba rock-ice avalanche were analyzed. This study suggests that the long-term effect, including historical seismic effects and freeze-thaw action, are the key factors for this landslide occurrence. Some interesting landforms and sedimentary structures, such as lateral ridges, superelevation, and boat rocks, were found in this case and were used to explain the characteristics of the velocity and the thinning spreading process of the avalanche mass. The numerical simulation further reveals the entire movement of this rock-ice avalanche lasted about 105s, with a maximum front velocity of 82m/s. Based on the simulated result, landforms, and sedimentary characteristics, the underlying substrate rather than the ice body is considered to contribute to the hypermobility of the Ganheba rock-ice avalanche. The developed fissures, complex topography, and basal friction are determined to control the progressive fragmentation of this case. Meanwhile, the emplacement process of the Ganheba rock-ice avalanche could be divided into four stages: failure and acceleration stage, collision deceleration stage, deceleration spreading stage, and deformation stage. The finding from this study makes some contributions to the evolution of glacier-related hazards in the high mountain region.